The Impact of Stress on the Body and Mind Psychosomatic Approach and Methods to Combat Stress - Boboc, Cristina (New Trends in Psychology, 2023)
Stress affects both the body and mind, as well as the behavior. For this reason it is important to know what are the causes of stress, what are the effects, symptoms and psychosomatic manifestations, as well as the solutions, the ways to combat stress and methods of self-regulation. The way we ensure our personal resilience regarding daily challenges and high-impact events in our lives is critical. Thus, it will increase tolerance to difficult bodily sensations and suppressed emotions to reduce uncontrolled reactions in relationships with others and will increase our quality of life.By exploring the somatic dimension in psychology, we can expand our ability to connect with our body and emotions, to regulate our nervous system, and increase our capacity to connect with others. These therapeutic methods centered on the body and the emotions have an important role in managing stress, preventing burnout, various diseases and conditions, and recovering from trauma. The psychosomatic approach provides useful tools for regulating the nervous system, increasing resilience, reducing symptoms and improving our lives by promoting well-being and health.